(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bihar is one of the states of India having lowest health profile. The accessibility of health facility is very poor. Child bearing is one of the hazardous experiences that women engage in while bringing a new life to this world. It is often associated with complications that may cause morbidities, disabilities and mortalities. Skilled attendance at childbirth is crucial for decreasing maternal and neonatal mortality ,yet many women in low- and middle-income groups deliver outside of health facilities, without skilled help. The main conceptual framework in this field implicitly looks at home births with complications. The level of utilization of maternal and child healthcare in Bihar is low. Use of maternal health services is an effective means for reducing the risk of maternal morbidity and mortality, especially in places where the maternal and child health services utilization is poor. The main objective of this study is to assess the factors affecting utilization of Maternal and child health services in Bihar.